To solve the quadratic equation \(2x^2 + 4x = -12\), we first need to bring all terms to one side of the equation:
\[ 2x^2 + 4x + 12 = 0 \]
Next, we can simplify the equation by dividing all terms by 2:
\[ x^2 + 2x + 6 = 0 \]
Now, we can use the quadratic formula \(x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a}\), where \(a = 1\), \(b = 2\), and \(c = 6\):
-
Calculate \(b^2 - 4ac\): \[ b^2 = 2^2 = 4 \] \[ 4ac = 4 \cdot 1 \cdot 6 = 24 \] \[ b^2 - 4ac = 4 - 24 = -20 \]
-
Use the quadratic formula: \[ x = \frac{-2 \pm \sqrt{-20}}{2 \cdot 1} \]
-
Simplify \(\sqrt{-20}\): \[ \sqrt{-20} = \sqrt{20} i = \sqrt{4 \cdot 5} i = 2\sqrt{5} i \]
-
Substitute back into the formula: \[ x = \frac{-2 \pm 2\sqrt{5} i}{2} \]
-
Simplify further: \[ x = -1 \pm \sqrt{5} i \]
Thus, the solutions can be expressed as:
\[ -1 \pm i\sqrt{5} \]
The correct response from the choices provided is:
\(-1 \pm i\sqrt{5}\)